E-COMMERCE STORE HIKARU MANGACLOTH WEB-BASED MOBILE USING FRAMEWORK CODEIGNITER (Information Technology and Telematics, 2015)
Abstract - Along with the progress of time and the development of mobile technologies is rapidly increasing, then humans are required to follow the development of the technology itself. Hikaru store is a store that sells clothing patterned cartoon JAPAN, at this store all sales activities are still done manually. Where to process the booking transaction, and the preparation of reports still take a long time and inefficient. So often the data is not appropriate or even loss of data and many other cases. This research aims to generate mobile web apps that facilitate businesses in marketing their products as well as consumers shop hikaru mangacloth in the transaction. System development method used is the waterfall model and for the design of systems using UML. The software used is the program design using Adobe Dreamweaver, PHP MySQL as the database, as the CodeIgniter framework, and Apache as the web server. This research has resulted in the application JAPANESE clothing sales at stores mangacloth hikaru-based mobile web makes it easy for the customer or the customer in the transaction ordering japanese clothes or just look at Japanese apparel products that are sold along with price and product information. This app has been tested on the shop owner and the customer and the result is already a good system but need plus some menus. Keywords: E-Commerce, Mobile Web, Framework CodeIgniter Abstrak - Seiring dengan kemajuan zaman dan berkembangnya teknologi mobile yang semakin pesat, maka manusia dituntut untuk mengikuti perkembangan dari teknologi itu sendiri. Toko Hikaru adalah toko yang menjual pakaian bermotif kartun JEPANG, pada toko ini semua kegiatan  penjualan masih dilakukan secara manual. Dimana untuk  proses transaksi pemesanan, dan penyusunan laporan masih membutuhkan waktu yang lama dan tidak efisien. Sehingga sering terjadinya data yang tidak sesuai atau bahkan terjadi kehilangan data dan masih banyak kasus lainnya. Penelitian ini bertujuan menghasilkan aplikasi web mobile yang mempermudah pebisnis dalam memasarkan produknya serta konsumen toko hikaru mangacloth dalam melakukan transaksi. Metode pengembangan sistem yang digunakan adalah model waterfall dan untuk perancangan sistemnya menggunakan UML. Perangkat lunak yang digunakan adalah perancangan program menggunakan adobe dreamweaver, php MySQL sebagai database, codeigniter sebagai framework, dan Apache sebagai web servernya. Penelitian ini telah menghasilkan aplikasi penjualan pakaian JEPANG pada toko hikaru mangacloth berbasis web mobile yang memberikan kemudahan bagi customer atau pelanggan dalam melakukan transaksi pemesanan pakaian jepang atau sekedar melihat produk pakaian jepang yang di jual beserta harga dan keterangan produk. Aplikasi ini telah di uji cobakan kepada pemilik toko dan pelanggan dan hasilnya adalah sistem sudah baik tetapi perlu ditambah beberapa menu. Kata Kunci : E-Commerce, Web Mobile, Framework Codeigniter